Generalized Equivariant Cohomology and Stratifications. Issue 3 (1st September 2016) - Crooks, Peter; Holden, Tyler
Abstract: For T a compact torus and E_T^* a generalized T -equivariant cohomology theory, we provide a systematic framework for computing E_T^* in the context of equivariantly stratified smooth complex projective varieties. This allows us to explicitly compute H_T^*( X ) as an H_T^*( pt ) -module when X is a direct limit of smooth complex projective T_C -varieties. We perform this computation on the affine Grassmannian of a complex semisimple group.